Effect Of Social Media Tourism Information Quality On Travel Intentions: Mediation Effect Of Destination Image Formation (Case Study In Galeri Nasional Visitors) - Prianti, Diani Mustika; Ridwan, Okky Rizal; Jamaluddin, Mohd Raziff; Multazam, Muhammad Mas (Politeknik Pariwisata NHI Bandung, 2025)
The rapid development of information technology today makes the world seem to have no barrier to space and time. As one of the media for conducting conversations, social media has now developed into today's photo and video-sharing media. This study aims to analyze the effect of social media tourism information quality and destination image formation on tourists' decisions to visit the National Gallery of Indonesia. Furthermore, the method used in this research is a quantitative method with an explanatory format and assisted by Partial Least Square (PLS) statistical tools consisting of validity and reliability tests. Respondents in this study were 236 samples. Sampling was done using an accidental sampling technique on visitors who came by chance during the survey. Data analysis in this study used convergent validity and discriminant validity. The analysis results show that the amount of information, completeness, design, interest, relevance, timeliness, and added value affect the destination image, both affective and cognitive images.